Optimizing the Performance of the Safety and Security Unit of the Temanggung Police Traffic Unit Through Traffic Community Education to Prevent Traffic Violations (Indonesian Journal of Police Studies, 2024)
Traffic violations are a form of action that contradicts Law Number 22 of 2009 concerning Road Traffic and Transportation. One of the causes of traffic violations in Temanggung Regency is due to a form of mental indiscipline of the community towards the rules and discipline in traffic. In the last two years, traffic violations in Temanggung Regency have increased significantly. Thus, the Safety and security Unit of the Temanggung Police Traffic Unit needs to optimize performance to prevent traffic violations. The purpose of writing in this final project is to describe the performance through Traffic community education and efforts to optimize Traffic community education carried out by the Safety and security Unit to prevent traffic violations.  Conceptual literature uses several theories, including Management theory and SWOT analysis theory. While the concepts used, including the concept of Performance, the concept of Optimization, the concept of Traffic community education, and the concept of Traffic Violations. The research method uses a qualitative method with a descriptive type. Data sources include primary and secondary through observation, interviews, and document studies. Data validity was obtained using data triangulation. The research location is in the jurisdiction of Temanggung Police. The results of the research findings are (1) the performance of the Safety and security Unit is not optimal due to the lack of personnel awareness of administrative issues, the existence of personnel shortages, inappropriate targeting and not maximizing the Traffic community education, as well as the lack of supervision and controf Traffic community education activities and (2) efforts to optimize which are assessed from non-optimal Organizational Resources such as personnel who are lacking and not competent, the use of the budget is not optimal, facilities and infrastructure are lacking, and implementation methods are not optimal. The conclusions of the writing are (1) The performance of the Safety and security Unit which has not been optimal through Traffic community education to prevent traffic violations and (2) Efforts to optimize Traffic community education which have not been maximized in utilizing organizational resources carried out by the Safety and security Unit.
Keywords: Traffic community education; performance; prevention of traffic violation